Praanggapan dalam Tuturan Dialog Bahasa Persidangan di Pengadilan Negeri Kelas 1A Pekanbaru - Erni, Erni; Herwandi, Herwandi; Sari, Indah (Program Studi Pendidikan Bahasa dan Sastra Indonesia FKIP Universitas Islam Riau, 2019)
Interpersonal verbal communication will run fluently, if there is a continuity of the propositions spoken. Well-connection is a manifestation of the understanding between speaker and listener; understanding of information from utterances. This study examined the types of presupposition that appear in the speech of prosecutor with a witness in the Domestic Court of IA class, Pekanbaru. The classification of types of presupposition refers Yule’s theory in 1996. This research was descriptive study. To answer the research questions, data was collected through all the speeches of the prosecutor and witnesses during submission of witnesses in criminal case session in the Domestic Court of IA class, Pekanbaru. The results showed that there are four types of presupposition found from prosecutors’ speeches regard to Yule’s theory. Further, two types of presupposition that do not appear in the prosecutors’ speeches. These two presuppositions are caused by all the prosecutors’ speeches are based on factual information. The most frequencies of the presupposition are structural presupposition and the rare frequencies are factual presupposition. Structural presupposition is dominant because almost of prosecutors’ speeches contain of interrogative utterances mode.